Casimir force control with optical Kerr effect - Y.Y., Khoo; C.H., Raymond Ooi (Universiti Kebangsaan Malaysia, 2013)
The control of the Casimir force between two parallel plates can be achieved through inducing the optical Kerr effect of a nonlinear material. By considering a two-plate system which consists of a dispersive metamaterial and a nonlinear material, we show that the Casimir force between the plates can be switched between attractive and repulsive Casimir force by varying the intensity of a laser pulse. The switching sensitivity increases as the separation between plate decreases, thus providing new possibilities of controlling Casimir force for nanoelectromechanical systems.